Landscape connectivity affects individual survival in unstable patch networks: the case of a freshwater turtle inhabiting temporary ponds - Serrano, Filipe; Pita, Ricardo; Mota-Ferreira, Mário; Beja, Pedro; Segurado, Pedro (Freshwater Biology, 2019)
1. The loss of connectivity is among the main threats for species occupying freshwater pond networks. Landscape connectivity can impact the persistence of patchy populations by reducing movement rates among ponds, thereby increasing the likelihood of local extinctions in source–sink systems, and reducing the probability of colonisation following extinctions. In addition, loss of connectivity may also reduce survival rates if individuals have to cross a hostile matrix, though this hypothesis has been rarely tested. Here, we address these issues by evaluating how individual survival and inter-patch movement probabilities of the European pond turtle (Emys orbicularis) are influenced by patch connectivity. 2. The study was carried out in a network of temporary ponds embedded in a heterogeneous agricultural matrix in southwestern Portugal, encompassing a period associated with a severe drought (2003–2005) and another with wetter climatic conditions (2010–2014). We mapped the location of ponds and land uses around each pond, and quantified connectivity among ponds using least-cost distances based on patch location and resistance to movement of different land uses. We then used multistate capture-recapture modelling to quantify how survival and movement of this freshwater turtle were related to different metrics of landscape connectivity, in the wet and dry periods. 3. We captured 221 pond turtles, including 89 juveniles, 58 females, and 74 males. Survival was higher in ponds more connected with other ponds, especially for juvenile turtles. The probability of movement between ponds decreased with increasing least-cost distances. Movement probabilities tended to be higher in the dry than in the wet period. 4. Our results support the idea that landscape connectivity affects both movement and survival rates in a patchy population inhabiting a temporary pond network. These effects are likely to be particularly marked in unstable freshwater systems like ours, where individuals may have to move widely to escape drying pond during particularly dry years.5. Overall, our findings suggest that focusing conservation efforts solely on protecting discrete freshwater habitats such as temporary ponds may be insufficient, requiring also due consideration of landscape connectivity offered by the surrounding agricultural matrix to assure long-term persistence of patchy populations inhabiting such habitats.
Keywords: Capture-recapture; Emys orbicularis; Fragmentation; Habitat patches; Movement